Enhancement of UMKM Financial Management in Kec. Cilawu For Supporting The Halal Ecosystem - Ira Siti Rohmah Maulida; Arif Rijal Anshori; Neng Dewi Himayasari; Iwan Permana (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Most of the small traders in Cilawu are trapped by loan sharks. This condition is due to limited literacy and legal sources of capital. Still need to gain confidence in sharia financial service products. This study concludes the Enhancement of the Ability of UMKM Financial Management in Cilawu For Supporting The Halal Ecosystem is to increase literacy in financial management for traders, from planning to preparing financial reports that because the level of financial literacy of traders is still low, and traders do not have confidence in financial service institutions and financial service products; besides that, it is necessary to provide literacy in Islamic financial institutions and their financial products and services, which can directly boost the activities of Islamic financial institutions to contribute to the development of the halal ecosystem.